An agroecologically oriented introduction of cassava germplasm from Latin America into Africa - Porto, M.C.; Asiedu, Robert; Dixon, A.; Hahn, S.K. (International Society for Horticultural Science, 1994)
An agroecologically-based germplasm enhancement strategy to further broaden the genetic base of cassava in selected ecologies of Africa was initiated by CIAT and IITA in 1990. Crosses are being made at CIAT, in Colombia, using parents adapted to four different agroecologies of South America with homologues in Africa. Selection of parents is made on the basis of resistance to pests and specific quality traits such as low cyanide content, yellow root flesh, and mealiness. Resistance to ACMD is being incorporated by using IITA elite clones introduced to CIAT as parents. To date, a total of 130 000 botanical seeds comprising 725 families have been introduced into Nigeria through IITA. Three seedling nurseries were established in 1990 at locations representing the subhumid (Ibadan), humid (Onne), and semi-arid (Kano) ecologies. In 1991, a nursery was also established in Jos, a midaltitude location, in Nigeria. Establishment of seedlings was successful even under severe environmental conditions such as those existing at Kano, where a dry period of 6 months was experienced by the seedlings. Reaction to pests and diseases and growth of individual seedlings were monitored at monthly intervals during 1990–91. Pressure of CBB and ACMV was higher at Ibadan between July and November, but general recovery of individuals with symptoms of ACMD was observed during the dry season. A better reaction in the progenies resulting from the crosses involving IITA clones TMS 30001 and TMS 30572 was observed. Plant growth was fastest in the population evaluated at Onne and slowest at Kano, although at the latter location plants also continued to grow during the dry season. Comparison within families across environments was only possible at Ibadan and Onne, since the population evaluated at Kano was different from the other two. Individuals selected at the seedling stage are being cloned by IITA and will be evaluated progressively following the IITA cassava scheme.